“A Weasel Pops In and Out of Old Tunes”:: Exchanging Words - Baker, Marie; Grauer, Lally (Studies in Canadian Literature)

(untitled) (The University of New Brunswick, 2006)
Marie Annharte Baker refuses the roles of educator and informant partly through her strategy of scavenging, replacing and exchanging words. As she encourages readers to seek out their own meanings, she promotes agency, diversity and—perhaps most importantly—rediscovery. In poems such as “Bird Clan Mother,” “Raced Out to Write This Up,” and “Coyote Columbus Café,” Baker contextualizes the language of social control to express outrage with the polite Canadian impulse to remain silent and not challenge racist assertions. By mocking the absurdity of racial classifications which occur in everyday conversations and academic discourse, the poet seeks to draw attention to the many barriers that are employed to exclude the ‘Other’ in English.